Effect of Developmental Therapy on the Psychomotor Development in Preterm Infant (Bangladesh Journal of Child Health, 2017)
Background: Preterm brain is prone to hypoxia and other insults that result in psychomotor delay. Early intervention in the form of developmental therapy in preterm babies reduces the subsequent psychomotor delay. A study was conducted to evaluate the psychomotor developmental outcome of preterm infant who got developmental therapy.Objective: To evaluate the psychomotor developmental outcome of preterm infant who will be getting developmental therapy.Methods: It was a quasi experimental study (single group pretest/post test design). It was carried out among the preterm babies who attended within 6-12 weeks of age for developmental assessment at the Centre for Neuro Development & Autism in Children (CNAC) Bangabandhu Sheikh Mujib Medical University (BSMMU) during the period of July 2010 to September 2011. Forty five preterm infants were assessed for their motor, mental & behavior score by Bayley Scale of Infant Development II, (BSID) (1993) Bengali version). All of them got Developmental therapy regularly as per demonstration in both home and Hospital. Their base line assessment was done at 6-12 weeks of age and reassessed at 3 months and 6 months after developmental therapy.Results: Thirty seven (82.2%) infants have completed the two follow up session. At 6 months of developmental therapy 54.1% had motor skill improvement, 40.5% had mental skill improvement and 48.6% had behavior skill improvement. Socio economic status and illness in neonatal period had some influence on developmental out come.Conclusion: Developmental Therapy improved the psychomotor development in preterm infant.Bangladesh J Child Health 2016; VOL 40 (3) :149-153